The Handling of the Rectal Stump Does Not Affect Severe Morbidity After Subtotal Colectomy For Ulcerative Colitis: A Retrospective Cohort Study. (September 2020) - Lissel, M.; Omidy, S.; Myrelid, P.; Block, M.; Angenete, E.
Background and Aims: Colectomy due to ulcerative colitis is associated with complications. One severe complication is the risk for blow-out of the remaining rectal remnant. The aim of this study was to compare the frequency and severity of complications in patients with the rectal remnant left subcutaneously versus patients with the rectal remnant left intra-abdominally. A secondary aim was to identify risk factors for complications. Materials and Methods: Consecutive patients at two tertiary centers in Sweden were retrospectively reviewed regarding surgical procedures; complications classified according to Clavien–Dindo; and possible risk factors for complications such as preoperative medication, emergency surgery, and body mass index. Results: 307 patients were identified. Minor complications were more common than previously reported (85%–89%). Severe surgical complications were not related to the handling of the rectal remnant. Leaving the rectal remnant subcutaneously was associated with local wound problems. Risk factors for severe complications were emergency surgery and preoperative medication with 5-aminosalicylic acid. Conclusion: Minor complications after colectomy for ulcerative colitis are very common and need to be addressed. Leaving the rectal stump intra-abdominally seems safe and may be advantageous to reduce local wound morbidity.